Optimal (R, Q) policy and pricing for two-echelon supply chain with lead time and retailer's service-level incomplete information - M. Esmaeili; M. S. Naghavi; A. Ghahghaei (Journal of Industrial Engineering International, 2018)
Many studies focus on inventory systems to analyze different real-world situations. This paper considers a two-echelon supply chain that includes one warehouse and one retailer with stochastic demand and an up-to-level policy. The retailer's lead time includes the transportation time from the warehouse to the retailer that is unknown to the retailer. On the other hand, the warehouse is unaware of retailer's service level. The relationship between the retailer and the warehouse is modeled based on the Stackelberg game with incomplete information. Moreover, their relationship is presented when the warehouse and the retailer reveal their private information using the incentive strategies. The optimal inventory and pricing policies are obtained using an algorithm based on bi-level programming. Numerical examples, including sensitivity analysis of some key parameters, will compare the results between the Stackelberg models. The results show that information sharing is more beneficial to the warehouse rather than the retailer.
Keywords: 650; Two-echelon supply chain; Incomplete information; Lead time; Transportation cost; Service level